“Enhancing Regional Cooperation through Customs Digitalization in CEFTA- 2006” - Kocev, Ljuben; Kikerkova, Irena; Toshevska trpchevska, Katerina; Makrevska disoska, Elena (Faculty of Economics and Business, University of Zagreb, Zagreb, 2019)
The past decade of the existence and functioning of the CEFTA - 2006 has indicated that the performances of its members in regard to regional economic integration and trade liberalization have been unsatisfactory. The statistics point out that within the 12-year period of the creation of the CEFTA - 2006 the integrative process is at a standstill. In July 2017, under the so-called Berlin process, representatives of the CEFTA Parties, met in Trieste and decided to enhance the regional cooperation with the creation of regional economic area – an area which should not only eliminate all trade and non-trade barriers in trade in goods, but should also lead to complete liberalization of trade in services, capital and labor as well as digital integration. In order to achieve this, an Additional Protocol 5 to the Agreement on Amendment of and Accession to the Central European Free Trade Agreement has been signed, while Additional Protocol 6 is also planned to be signed and integrated in the following period. This paper will give a brief overview of the trade liberalization achieved within the CEFTA-2006, and the obstacles that were detected which prevented further regional integration. It will then focus on the Additional Protocol 5 and the further requirements on trade facilitation provided therein and will particularly focus on the process of digitalization with the aim of deeper regional economic integration.
Keywords: CEFTA-2006, Additional Protocol 5, Regional Economic Area, trade facilitation, digitalization